The great liquidity freeze: What does it mean for international banking? - Dietrich Domanski; Philip Turner (Asian Development Bank Institute (ADBI), 2011)
In mid-September 2008, following the bankruptcy of Lehman Brothers, international interbank markets froze and interbank lending beyond very short maturities virtually evaporated. Despite massive central bank support operations and purchases of key assets, many financial markets remained impaired for a long time. Why was this funding crisis so much worse than other past major bank failures and why has it proved so hard to cure? This paper suggests that much of that answer lies in the balance sheets of international banks and their customers. It outlines the basic building blocks of liquidity management for a bank that operates in many currencies and then discusses how the massive development of foreign exchange (forex) and interest rate derivatives markets transformed banks' strategies in this area. It explains how the pervasive interconnectedness between major banks and markets magnified contagion effects. Finally, the paper provides some recommendations for how strategic borrowing choices by international banks could make them more stable and how regulators could assist in this process.
Keywords: E44; G01; G15; G18; G24; G28; 330; Geldmarkt; Internationale Bank; Risikomanagement; Bankenliquidität; Bankrisiko; Ansteckungseffekt; Welt